2022
DOI: 10.3390/antibiotics11121752
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Disulfiram as an Antimicrobial Agent in Topical Infections

Abstract: Antimicrobial drugs applied topically offer several advantages. However, the widespread use of antibiotics has led to increasing antimicrobial resistance. One interesting approach in the drug discovery process is drug repurposing. Disulfiram, which was originally approved as an anti-alcoholism drug, offers an attractive alternative to treat topical multidrug resistance bacteria in skin human infections. This study aimed to evaluate the biopharmaceutical characteristics of the drug and the effects arising from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The key aspects of the disulfiram mode of action that could explain its antifungal activity can be understood by two effects. First, disulfiram is a chelator agent that can sequester copper and consequently alter various metabolic pathways in cells; and second, D has an affinity for the thiol groups of cysteine residues in several cellular targets [ 21 , 22 ]. D may be considered a potential agent for the treatment of candidiasis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The key aspects of the disulfiram mode of action that could explain its antifungal activity can be understood by two effects. First, disulfiram is a chelator agent that can sequester copper and consequently alter various metabolic pathways in cells; and second, D has an affinity for the thiol groups of cysteine residues in several cellular targets [ 21 , 22 ]. D may be considered a potential agent for the treatment of candidiasis.…”
Section: Resultsmentioning
confidence: 99%
“…In other permeation studies involving human and pig skin, D showed a lack of permeability [ 21 , 22 ]. These differences are due to the nonkeratinization of the vaginal epithelium, and the increase in surface area provided by the transversal rugae of the mucosa would also increase drug absorption across this tissue [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations